Urgensi Pengaturan Sita Aset Perkara Pidana Korupsi dalam Rangka Pemulihan Aset Negara - Ferdian, Tomy; Hafrida, Hafrida; Sudarti, Elly (AL-SULTHANIYAH, 2026)
Corruption in Indonesia has transformed into an extraordinary crime that systemically destroys the state's economic structure. Despite a high rate of law enforcement actions, the level of asset recovery remains very low compared to the total state financial losses incurred. This research aims to analyze the urgency of updating the legal framework regarding asset confiscation in corruption cases in Indonesia. The method used is normative juridical research with statutory and conceptual approaches. The findings indicate that the current asset confiscation regulation, which relies on the Criminal Procedure Code (KUHAP), focuses solely on evidentiary purposes (corpus delicti) and requires an in personam claim, making it inadequate for the optimal recovery of state losses. Furthermore, there is a disharmony of norms between the KUHAP, the Anti-Corruption Law, and bankruptcy law, which frequently hinders the asset execution process. Therefore, legal reformulation through the adoption of the Non-Conviction Based (NCB) Asset Forfeiture principle is an absolute necessity. This concept allows for asset confiscation without waiting for a criminal conviction against the perpetrator and is proven to be in line with international standards such as UNCAC and FATF. This research concludes that the enactment of the Asset Confiscation Bill is highly urgent and must be accompanied by institutional legal harmonization and mechanisms to protect the civil rights of good-faith third parties.